INTEGRATING INTERACTIVE METHODS AND MODERN PEDAGOGICAL TECHNOLOGIES IN FINE ARTS EDUCATION - Muratova Dilnavoz Jamshid qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
The integration of interactive methods and modern pedagogical technologies in fine arts education has significantly transformed traditional teaching practices. This approach combines innovative teaching strategies with digital tools andinteractive techniques to enhance student engagement, creativity, and learning outcomes. The article examines the methodological principles and practical applications of integrating interactive methods and modern technologies in art education. The study highlights how this integrated approach promotes active learning, critical thinking, and the development of artistic competencies. Findings suggest that the use of interactive and technology-enhanced pedagogies supports a learner-centered environment, increases motivation, and fosters both creative and analytical skills among students.